(untitled) - Kim, W. Chan (Boston, Massachusetts, 2017)
Blue ocean leadership works because the managers' "customers"--that is, the people managers oversee and report to--are involved in identifying what's effective and what isn't. Moreover, the approach doesn't require leaders to alter who they are, just to undertake a different set of tasks. And that kind of change is much easier to implement and track than changes to values and mind-sets.
Keywords: Lãnh đạo,Leadership